Time Dependent Development of Aluminium Pitting Corrosion - Robert E. Melchers (Advances in Materials Science and Engineering, 2015)
Aluminium alloys have excellent corrosion resistance to a wide variety of exposure conditions. Usually they corrode by pitting rather than by uniform corrosion. For infrastructure applications long-term corrosion behaviour is of interest. The relatively limited long-term pitting data that is available shows that maximum and average pit depths do not follow the power law function as conventionally assumed but tend to follow a bimodal trend with exposure time. This is consistent with the bimodal trends observed previously for corrosion mass loss of aluminium alloys. Most likely it is the result of the accumulation of corrosion products over the pit mouths, leading to the gradual development of localised anoxic conditions within pits. In turn this permits the development within the pits of anoxic autocatalytic conditions, consistent with established theory for pitting corrosion of aluminium. It also is consistent with observations of hydrogen evolution from pits. The implications of this for practical applications are discussed.